Black and White in the Print media: The Language of Bulgarian Rock Read in Transition - Bratanov, Emil (Media and Language, 2019)
Researching the marks left by the rock bands forming the Transition towards Democracy’s Second generation, the logical choice falls on the print media. Back then existed only one TV channel and one radio station. Both musicians and fans wanted to create a new art form. Printed press served as a mediator in this communication. Back then, digital media still haven’t surpassed printed word, which was the real “library of memories”. Time shows that this textual reality is the only trustworthy archive of the new “BG Rock” musicians generation from the end of the 80s. There are several questions which arise from this and which are worth the research. Do rock musicians manage to force on the print media their professional and highly specialized jargon and what was the role of rock journalists who were working in the period between 1987 and 1992/93? Would we be able to find a new style in Bulgarian print media? Would that style irritate the readers?
Keywords: rock; Bulgarian rock; media; media language; media style; second Bulgarian rock generation